DOES CORPORATE SOCIAL RESPONSIBILITY ADD VALUE TO THE INDIAN BANKING SECTOR? - Gaba, Nitika; Madhumathi, R. (Indian Journal of Finance and Banking, 2022)
Corporate social responsibility (CSR) is assumed to have an indirect impact on the performance of the banking sector due to the sector’s core non-manufacturing and complex functionalities. This paper examines the value creation for a bank through CSR initiatives considering their earnings persistence and risk exposure in India. The authors measure CSR disclosure through content analysis. CSR scores for 14 items are identified from the annual reports, National CSR Portal, Ministry of Corporate Affairs (MCA, 2021) and websites of 20 Indian banks. Applying OLS and panel regression models, the role of CSR in creating value for the banking sector is established. The study found that CSR commitment has a positive impact on the market value of the banks, along with an adequate liquidity position and business risk. CSR commitment and earnings persistence contribute to the bank’s expected operating performance, highlighting its sustainability through CSR investments. Participation of banks for education, healthcare, skill development, and environmental sustainability is associated with higher returns from their lending activities to customers creating social value addition. Specific CSR activities encourage bank customers to repay banks with the implication of business risk reduction for banks. JEL Classification Code: M14, G21.